UPAYA REHABILITASI HUTAN DAN PEMANFAATAN LAHAN KRITIS DI KALIMANTAN TIMUR BERDASARKAN PERATURAN DAERAH PROVINSI KALIMANTAN TIMUR NOMOR 6 TAHUN 2016 - David David (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT The foundation of forestry development is Article 33, Paragraph 1, 1945 Constitution which states that the earth and water and the natural resources contained therein are controlled by the State and used to the greatest extent possible for the prosperity of the people. The RPJPN mandates that the emphasis of the National Long Term Development Plan be placed on the economic sector, which is the main driver of development, along with the quality of human resources and encouraged mutually reinforcing, interrelated and integrated with the development of other fields carried out in rhythm, harmony and compatible with the success of economic development in order to achieve national development goals and objectives. Forestry development includes all efforts to utilize and strengthen the function of natural resources of forests and other living natural resources and their ecosystems. Both as a protector of the life support system and preservation of biodiversity as well as development resources. Thus forestry development includes aspects of preservation of environmental functions, economic development and social welfare, both inside and outside the state forest. According to its function, forests are divided into production forests, convertible production forests (conversion forests), protected forests, natural reserve forests and tourist forests. Critical forest and land rehabilitation system in East Kalimantan: (1) Planting cover crops such as multiple cropping systems. Complementary livestock and food crops, and integrated business of livestock and fruit gardens (2) Processing of land according to contour lines (3) Making of terraces namely credit terraces, concrete terraces, and bench terraces (4) Making deadlines (rorak) (5) to regulate cropping patterns (crop rotation): Making terraces namely bench terraces, making dead-end channels, making surface flow control channels, developing agroforestry, reforestation and reforestation, so that critical land management efforts require land conservation efforts. Land conservation is an effort to prevent damage, repair damage, maintain and maintain land fertility and increase soil fertility. Then a Conservation Farmer Business is carried out, namely a farming model that applies conservation principles.